Pathogenicity Efficacy of Entomopathogen Fungus Beauveria bassiana Against In Vitro Rice Stem Borer (Scirpophaga innotata) - Syahbudin Hasibuan; Zulfahmi Simbolon; Ifan Aulia Candra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
White rice stem borer (Scirpophaga innotata) is one of the dangerous pests for rice (Oryzae sativa) because it attacks rice stems that can cause 50% loss of total production. The purpose of this study was to determine the pathogenicity of Entomopathogen Fungus Beauveria bassiana at different conidia dilutions (J), namely J1 (105), J2 (106), J3 (107), J4 (108), and J5 (109). The mortality of S. innotata larvae was tested with the density of B. bassiana of 2.08 × 106 conidia/ml. The effect of B. bassiana on the success transformation of S. innotata larvae to pupae for 14 observation day was also observed at the same B. bassiana density. This research resulted in the optimal pathogenicity of B. bassiana at dilution of 107 (treatment J3) which caused 100% death and 100% successful pupation. The lowest treatment was J5 (109 dilution) with a mortality rate of 50% and a successful pupation of 20%. The results of the probit analysis showed that the fastest average lethal time (LT50) value was found in treatment of 107 (J3) which reached 11.11 h. Keywords: Beauveria bassiana, Pathogenicity, Probit analysis, Scirpophaga innotata.